BEYOND REGULAR ELECTIONS: A DEBATE ON THE DEMOCRATIC CONTEXT IN SÃO TOMÉ AND PRÍNCIPE - Santos, Ayolsé Andrade Pires dos (2023)
After gaining independence in July 1975, São Tomé and Príncipe lived under a one-party regime. Given the socioeconomic failure during the 15 years of single-party rule and political conflicts between party members, the country boosted the democratization process in 1990. More than 30 years after the implementation of democracy, there were several failures in this process. No matter how democracy in São Tomé and Príncipe has been restructured, the organization of the State has failed to respond to the social problems that plague the country. Also, since democracy was implemented, the country has held regular elections without any conflicts of recognition or acceptance of election results between parties, which proves in a certain way, the good functioning of democracy. In this context, the question arises: why is São Tomé and Príncipe as a democratic country with regular elections, underdevelopment has been its main characteristic? Using the bibliographic analysis method, this study aimed mainly by reflecting on the current state of democracy in São Tomé and Príncipe and its inability to promote socioeconomic development. As for the specific objectives, the aim was to: a) discuss political instability which constitutes an obstacle to the advancement of democracy and b) verify the weak participation of civil society in the democratic system that contributes to the current state of poverty in São Tomé and Príncipe. In this study, the data collected and analyzed were secondary data, which allowed the creation of graphs and tables to enable our analysis.